Unfractionated heparin reduces hepcidin levels in critically ill patients. Issue 5 (27th May 2021) - Vagionas, Dimitrios; Politou, Marianna; Kompoti, Maria; Papadakis, Dimitrios‐Dorotheos; Kostakou, Eirini; Theodoulou, Danai; Kaniaris, Evangelos; Rovina, Nikoletta; Koutsoukou, Antonia; Vasileiadis, Ioannis
Abstract : A strong anti‐hepcidin activity has been observed in heparins. Mean hepcidin levels were significantly reduced compared to baseline, following the first day of unfractionated heparin administration in critically patients. Heparin displayed a strong independent negative association with hepcidin. These results may lead to future treatment methods of forms of anaemia characterised by hepcidin excess, common among the critically ill.